Mapping QoS classes in loose coupling heterogeneous networks - Ousta, F. (Maxwell Science Publications, 2014)
One of the main objectives of Heterogeneous Wireless Access Networks (HWAN) is to integrate the different wireless access technologies, such as Universal Mobile Telecommunication System (UMTS), Worldwide Interoperability for Microwave Access (WiMAX) and Wireless Local Area Network (WLAN), with a common IP-based network in order to offer mobile users continuous and unified service in a transparent way. However, one of the major issues is to support end-to-end Quality of Service (QoS) across all these technologies at all stages of the service from set-up to handoff. We present, in this study, a novel method of mapping QoS of UMTS and WiMAX over a loose coupling environment across Internet Protocol/Differentiated Service (IP/DiffServ) network. Â© Maxwell Scientific Organization, 2014.